The challenges of COVID-19 in nursing education: The time for faculty leadership training is now. (August 2020) - Singh, Ashley; Haynes, Melanie
Highlights: Nursing faculty have an influential and critical role in both classroom, clinical, and university setting. Faculty must engage in leadership training to be able to master the ever-evolving complex challenges of the faculty role. Leadership training is critical for faculty, student, and university success.